2016
DOI: 10.17113/ftb.54.04.16.4497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polyphenols and Antioxidant Capacity of Fruits and Vegetables Using a Modified Enzymatic Extraction Method

Abstract: Fruits and vegetables are an essential part of the human diet, and several epidemiological studies show that the content of natural antioxidants, especially fl avonoids, may be benefi cial in protecting the human body against damage induced by reactive species. This is important for maintaining physiological redox equilibrium (1,2). These foods supply several antioxidants, such as ascorbic acid (vitamin C), tocopherols and tocotrienols (vitamin E), carotenoids (provitamin A), and several phenolic compounds (fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
2
19
0
2
Order By: Relevance
“…Mango is rich in xanthones and flavonols, and most of the phenolic compounds exist in peel [23], and blueberry rich in phenolic acids, flavonoids and anthocyanins [24]. Similar trends but with higher values in TPC were reported previously in Chile fruit samples (harvested from Santiago, Chile) like blueberry (4.75 ± 0.34 mg GAE/g) and strawberry (4.02 ± 0.14 mg GAE/g) compared to pear (0.99 ± 0.07 mg GAE/g) extracted with different solvent methanol [25]. These higher TPC values might be due to the difference of fruit grown at different climate and region also extracted with different solvent.…”
Section: Resultssupporting
confidence: 80%
“…Mango is rich in xanthones and flavonols, and most of the phenolic compounds exist in peel [23], and blueberry rich in phenolic acids, flavonoids and anthocyanins [24]. Similar trends but with higher values in TPC were reported previously in Chile fruit samples (harvested from Santiago, Chile) like blueberry (4.75 ± 0.34 mg GAE/g) and strawberry (4.02 ± 0.14 mg GAE/g) compared to pear (0.99 ± 0.07 mg GAE/g) extracted with different solvent methanol [25]. These higher TPC values might be due to the difference of fruit grown at different climate and region also extracted with different solvent.…”
Section: Resultssupporting
confidence: 80%
“…Despite the lifelong pressure put upon our antioxidant defenses, fortunately antioxidants also exist in a variety of natural sources that we can ingest through our diet. For example, foods rich in polyphenols [ 107 ], carotenoids [ 108 ], lycopene [ 109 ], vitamins (A, C and E) [ 110 ], and flavonoids [ 111 ], have all been shown to support the body’s natural antioxidant defenses. It is due to the benefit of these naturally occurring antioxidants that antioxidant-containing foods and supplements have been well researched [ 44 , 112 , 113 ] and used as a therapeutic strategy for the treatment of many diseases.…”
Section: Possible Application Of Creatine For the Promotion Of Vasmentioning
confidence: 99%
“…Studies to date concerning A. chinensis have mainly focused on its genome profiling and factors affecting the quality, bioactive constituents, and bioactivities of the fruit flesh (68). Extensive studies have reported the isolation and characterization of phenolic components of kiwifruit flesh by thin-layer chromatography, high performance liquid chromatography and ultra-high performance liquid chromatography (9, 10). Apart from the antioxidant activity, kiwifruit has also shown antimicrobial activity against many pathogenic bacteria: Pseudomonas aeruginosa , Escherichia coli , Listeria monocytogenes , and Staphylococcus aureus (11).…”
Section: Popular Scientific Summarymentioning
confidence: 99%